Sistem Informasi E-Arsip Tugas Akhir Berbasis Web Pada Perpustakaan Institut Teknologi Dan Bisnis Bina Adinata - Dana Wardana; Muhammad Awal Nur; sri asfirawati khalik (Journal System Information And Computer, 2025)
This research aims to: (1) Designing a website-based final project E-Archive information system at the Bina Adinata Institute of Technology and Business library. (2) Knowing the implementation of the website-based final project E-Archive information system design in the Bina Adinata Institute of Technology and Business library. This research uses the Waterfall research method, where stages are as follows: (1) Requirement Analysis and Definition (2) System and Software Design (3) Implementation and Unit Testing (4) Integration and System Testing (5) Operation and Maintenance. Based on the research results it can be concluded that: (1) Web-based final project E-Archive information system at the Bina Adinata Institute of Technology and Business library in its design using a system design model, namely the Unified Modeling Language (UML) including use case diagrams, activity diagrams and sequence diagrams, class diagrams. The programming language used is PHP and MySQL as its database storage with the system development method used waterfall. System testing used is the blackbox method and Usability Testing. (2) Implementation of a web-based final project E-Archive Information System at the Bina Adinata Institute of Technology and Business library is done well. This can be seen from the results of system testing using the System Usability Scale (SUS) method with a value of 72.9 which means grade scala B or included in the Good category.